Build and Improve the Vocational Training Staff in order to Meet the Requirements for the Three Levels of Training - Vũ Xuân Hùng; Cao Văn Sâm (Journal of Technical Education Science, 2006)
Since the Educations Law 2005 was promulgated, the vocational training system has been innovated with 3 skill levels: elementary, secondary, and college. This also put a question on how to build and improve the vocational training staff in order to overcome concurrent weaknesses and meet the requirements for the 3 level training. This article is about several researches in this issue.